Essays on alliances, antitrust immunity, and carve-out policy in international air travel markets - Thomas, Tyson (Kansas State University, 2015)
This dissertation seeks to answer questions regarding changes in the competitive environment in international air travel markets which has undergone rapid changes since the early 1990s. Specifically, the research in this dissertation examines policies regarding cooperation among airlines in international air travel markets as well as how cooperation affects an airline's product quality. These issues are explored in two essays which comprise my dissertation. The first essay explores the efficacy of a policy known as a carve-out. Airlines wanting to cooperatively set prices for their international air travel service must apply to the relevant authorities for antitrust immunity (ATI). While cooperation may yield benefits, it can also have anti-competitive effects in markets where partners competed prior to receiving ATI. A carve-out policy forbids ATI partners from cooperating in markets policymakers believe will be most harmed by anti-competitive effects. We examine carve-out policy applications to three ATI partner pairings, and find evidence of tacit collusion in carve-out markets in spite of the policy, calling into question whether consumers benefited from application of the policy in the cases studied. The second essay examines the relationship between product quality and airline cooperation. Much of the literature on airline cooperation focuses on the price effects of cooperation. The key contribution of our paper is to empirically examine the product quality effects of airline cooperation. Two common types of cooperation among airlines involve international alliances and antitrust immunity (ATI), where ATI allows for more extensive cooperation. The results suggest that increases in the membership of a carrier's alliance or ATI partners are associated with the carrier's own products having more travel-convenient routing quality. Therefore, a complete welfare evaluation of airline cooperation must account for both price and product quality effects.
Keywords: Economics; Econometrics; Airline Competition; Economics (0501)